Ideaship : how to get ideas flowing in your workplace - Foster, Jack, 1930-; Corby, Larry (San Francisco : Berrett-Koehler Publishers, 2001)
Defines an idea as "nothing more nor less than a new combination of old elements." This book uses that definition to discuss how to get them. Its 7 chapters deal with things you must do to condition your mind to be ripe and ready for idea creation. It also details the actions that you make in order to get an idea.
Preface; Part I: What Is Ideaship?; Part II: How Do You Become an Ideaist?; Part III: Sixteen Personal Things You Can Do; Part IV: Seven Organizational Things You Can Do; Part V: Eighteen Strategic Things You Can Do; What Should You Do Next?; Notes; Index; About the Author; About the Illustrator.
Includes bibliographical references (pages 127-129) and index.
English.
eBooks on EBSCOhost
Keywords: Creative ability in business; Psychology, Industrial; Management; Psychology, Industrial; Créativité dans les affaires; Psychologie du travail; Gestion; management; BUSINESS & ECONOMICS -- Leadership; Creative ability in business; Management; Psychology, Industrial